Eulerian Modeling of Lateral Solid Mixing in Gas-fluidized Suspensions. (2015) - Oke, Oyebanjo; Lettieri, Paola; Salatino, Piero; Solimene, Roberto; Mazzei, Luca
Abstract: We used the Eulerian-Eulerian modeling approach to investigate lateral solid dispersion in fluidized beds. To estimate the lateral dispersion coefficient ( D sr ) we fitted the void-free solid volume fraction radial profiles obtained from the numerical simulations of multifluid models with those obtained analytically by solving Fick's law. The profiles match very well. The values of D sr obtained numerically are larger than the experimental ones, but the two do have the same order of magnitude. We believe that the overestimation is due to how we modeled the frictional solid stress; we used the kinetic theory of granular flow (KTGF) model for the frictional solid pressure and the model of Schaeffer[20] for the frictional solid viscosity. To investigate how sensitive the numerical results are on the constitutive model used for the frictional stress, we ran the simulations again using a different frictional stress model, and changing the solid volume fraction at which the bed is assumed to enter the frictional flow regime ( ϕ min ). We observed from the results that D sr is quite sensitive to ϕ min . This is because the latter influences the size and behavior of the bubbles in the bed. We obtained the best predictions for D sr when ϕ min is 0.50. The results show that accurate prediction of lateral solid dispersion in fluidized beds depends on adequate understanding of the frictional flow regime, and accurate modeling of the parameters that characterize the latter, in particular the frictional pressure